Influence of Digital Technologies on Transition to a Circular Economy in Tourism: Values and Barriers - NASSANBEKOVA, Samalgul; YESHENKULOVA, Gaukhar; IBADILDIN, Nurkhat (Journal of Environmental Management and Tourism, 2023)
Circular economy (CE) designed as a socio-economic system where resources are maintained for a long term with minimal leakage and waste, making them circular through closing, narrowing and slowing resource loops. In this system, we should not only consider materials and technical resources but also human capital. Creating circular business strategies is one of the paradigms of sustainable development and has potential to achieve many of the SDGs. Digital technologies (DT) enable this movement to CE including in the service sectors as a tourism. The aim of this paper is to identify how DT supports the transition to CE in tourism (CET). In this study, we conducted semi-structured interviews with 12 experts from tourism, CE and DT fields. Findings determined main values created by DT in CET, with special attention to values for human development, and existing barriers to utilize whole potential of DT for CET. This study contributes to conceptualization of knowledge about the role of digitalization in transition to CE in tourism and outlines future research areas. Structured abstract : Purpose: to show how DT aids in the transformation of tourism to CE business model, by examine values created by DT for CE in tourism and human development and determine barriers for DT in transition to CE in tourism. Design/methodology/approach : In this study, we applied semi-structured interviews with experts. To address study subjects, we employed a non-random judgment sampling strategy. Twelve specialists in total participated in semi-structured interviews. Findings : Enhancing community participation, provide educational and training resources, access to information about sustainable tourism practices – are values created by DT for social development in tourism. Findings from the study suggest that DT can provide platforms for collaboration and innovation in tourism development. This can lead to new business models, products, and services that are more sustainable, inclusive, and resilient. However, in order to utilize DT in CET more effectively required particular economic, social, legal conditions, in the other word there are barriers and challenges. Originality : The present study reveals roles of DT for transition to CE in tourism particularly outlining human-centered approach. The exciting frameworks considering links between DT and CE in the literature mainly directed for closing, narrowing and slowing material resource flow and only few included human capital. In this study, we outlined the main DT important for transition to CE in tourism, values created by this DT for CE and human development in tourism and existing barriers for them.